Manajemen Wakaf Berbasis Teknologi Blokchain Dalam Meningkatkan Produktifitas Nadzir dan Kebijakan Sustainable Development Goals - Ermi Suryani; Azizah Mursyidah (LPPM Institut Nasional Laa Roiba Bogor, 2020)
This study aims to examine the management of waqf-based blokchain technology in increasing nadzir productivity and sustainable development goals policies. The method used is a qualitative analytical method with content analysis and data sources is a fact that occurs in waqf management based on blockchain technology taken through observation, interviews and literature review. The results of the study found that the management of Waqf by using blockchain technology was able to increase the income of waqf funds because it guaranteed the transparency between waqf and nadzir. This year the Indonesian Waqf Agency is in the process of blockchain technical towards increasing productivity this year and going forward. Obstacles BWI applies blockchain technology in Indonesia due to the lack of waqf human resources with expertise in technology. In realizing blockchain technology in its data institutions, the results of the National Coordination Board of Indonesia Waqf Board results were delivered by the Deputy Chairman of BWI, Imam Teguh Saptono. First, improve waqf literacy through various innovative programs. Like waqf to campus / school programs, including waqf material in the religious education curriculum and sermon themes. Second, building a national waqf information system that is integrated and easily accessible to the public. Third, utilizing information technology and financial market developments such as fintech, crowdfund, blockchain in collecting waqf. The fourth recommendation is the acceleration of the certification of waqf assets in the context of protecting national waqf assets. Fifth, increase professionalism and nadzir capacity through nadzir certification programs. Sixth, revitalizing the role of BWI as a national waqf nadzir institution. The seventh recommendation of the results of the National Coordination Meeting for Endowments in Indonesia, encouraging the acceleration of the revision of Law Number 41 of 2004 concerning endowments, and structuring or making BWI regulations as needed. Eighth, arrange BWI public service standards and improve the quality of BWI's human resources towards maximum public services. The ninth recommendation is to increase the synergy between BWI and the Ministry of Religion in advancing national representation. Tenth, improve coordination and synergy with law enforcement and waqf stakeholders in the context of protecting waqf assets. The eleventh recommendation is to carry out a memorandum of agreement between BWI representatives of districts, cities, provinces and BPN, districts, cities, provinces. The last recommendation is to appeal to individual nadzir to convert to nadzir legal entities. Productive waqf management using blockchain can improve the efficiency and effectiveness of waqf management from two sides. First, if waqf and Nazhir are connected to a blockchain system, then the donation transaction can be done with a high level of transparency. Secondly, if blockchain based waqf can reach global waqf waqf, then it is very possible for waqf from one country to represent in another country, especially a country that needs development funding. Keywords: Management of Waqf, Blockchain, Nadzir, SDG